Study protocol of “From Science 2 School”—prevalence of sports and physical exercise linked to omnivorous, vegetarian and vegan, diets among Austrian secondary schools - Wirnitzer, Katharina C.; Tanous, Derrick R.; Motevalli, Mohamad; Göbel, Georg; Wirnitzer, Gerold; Drenowatz, Clemens; Ruedl, Gerhard; Cocca, Armando; Kirschner, Werner (Frontiers in Sports and Active Living, 2022)
The increasing prevalence of unhealthy lifestyle choices contribute to almost all chronic conditions negatively affecting individual and public health. As the most beneficial preventative solution, a healthy lifestyle focusing on the dual approach of physical activity (PA) and a healthful diet is highly recommended. Considering the growing number of people interested in sustainable, plant-based diets, it seems crucial to analyze lifestyle behaviors with a special focus on diet type to delve deeper into the unenthusiastic health status among young populations. Therefore, this multidisciplinary study aims to survey and scale health behaviors with a special focus on the prevalence of traditional and vegetarian diets in connection with PA levels among Austrian pupils (10–19 years), teachers and principals in secondary education levels I and II. Following a cross-sectional design, sociodemographic and school-related data along with a complete profile of lifestyle behaviors, including detailed information regarding diet, PA, sports & exercise, and other health-related behaviors, were collected using online-based questionnaires. A total number of 8,845 children/adolescents ( 1.2% of the eligible 771,525 Austrian secondary school pupils) and 1,350 adults ( 1.5% of total eligible 89,243 Austrian teachers/principals) participated in the study. As this is the first investigation to explore the prevalence of veganism/vegetarianism amongst a large group of pupils, the present study will add an important contribution to overcome the lack of knowledge on PA, sports & exercise linked to healthy alternative diets. With a sustainable healthy lifestyle, a healthy transition from childhood to adulthood occurs, which can result in growing healthier functioning generations at all social levels. As a study protocol, the present article is intended to present comprehensive details of the study design, objectives, and the associated analytical procedures of the “From Science 2 School” study.